Comparative Study of Phytochemical and Antioxidant Potentials of Vernonia amygdalina, Carica papaya and Moringa oleifera Leaf Extracts for Livestock Use - Olufemi Joseph Banjoko; Martha Dupe Olumide; Lois Chidinma Ndubuisi-Ogbonna; Adeyinka Oye Akintunde (Jurnal Agro Veteriner, 2026)
Utilization of plants improve nutrient utilization and health. There is paucity of information on comparison of phytochemical and antioxidant potentials of Vernonia amygdalina, Carica papaya and Moringa oleifera leaf extracts. Leaves were air dried and soaked in 1.32 litres of absolute ethanol and placed on electronic shaker for 72 hours. The stock solution was filtered with muslin cloth, crude extract from the ethanol was then separated using rotary evaporator and dried at 40oC. Phytochemical and antioxidant analyses of the crude extract were then carried out using standard procedure. Results showed that the extracts contained glycosides, flavonoids, terpenoids, saponin, tannin, phytate and oxalate and varied significantly (P<0.05) in their antioxidants. Phenols (27.75±0.33), Flavonoids (2.97±0.01), FRAP (22.82±0.51), DPPH (63.89±1.55) and Vitamin C (60.19±0.17) had significant higher values in M. oleifera. It can be concluded that the plant extracts have very rich phytochemical and antioxidant compositions with potential to boost immunity in livestock.